Plasmonic Bi microspheres doped carbon nitride heterojunction: Intensive photoelectrochemical aptasensor for bisphenol A. (1st October 2019) - Yan, Pengcheng; Mo, Zhao; Xu, Li; Pang, Jingyu; Qian, Junchao; Zhao, Long; Zhang, Jianming; Chen, Jianping; Li, Henan
Abstract: Considering severe threat of bisphenol A (BPA) to environment and human health, it is urgent to develop a convenient and specific method for accurately detecting BPA. An efficient photoelectrochemical (PEC) aptasensor for determining BPA in water is constructed using Bi microspheres/carbon nitride (Bi/CN) heterojunction as a PEC material. The promoting effect of Bi on the enhanced PEC performance of Bi/CN heterojunction is initiated by two unique effects: the construction of heterojunction (heterojunction effect) and surface plasmon resonance (SPR) effect. For heterojunction effect, a metal-semiconductor heterojunction of Bi/CN is constructed, which increases the light absorption of CN, generates more electron-hole pairs and accelerates the separation of carriers. Simultaneously, as a plasmonic metal, Bi microspheres accelerate charge transfer generated from the heterojunction. This function of Bi is of high benefit to suppress the electron-hole recombination, leading to an enhanced PEC performance. Benefiting from enhanced PEC performance of the heterojunction, a sensitive PEC aptasensor for detecting BPA is realized. This work demonstrates that the Bi/CN heterojunction amplified photoelectric conversion strategy can be used as an efficient method for Bi-based materials to significantly enhance the PEC performance and also provides more opportunities for application of Bi-based materials in PEC field.